Boron neutron capture therapy (BNCT) translational studies in the hamster cheek pouch model of oral cancer at the new “B2” configuration of the RA‑6 nuclear reactor - Monti Hughes, Andrea (2017)
Fil: Monti Hughe,, Andrea. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes. Departamento de Radiobiología; Argentina